Interrelationships between environmental psychological factors and environmental behaviour among Malaysians - Neo, Sau Mei, 1990-, author; Choong, Weng Wai, 1981-, supervisor; Irina Safitri Zen, supervisor; Fakulti Alam Bina dan Ukur (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Ph.D (Pengurusan Fasiliti)) - Universiti Teknologi Malaysia, 2019